Rigvedic Fire Symbolism in Panchasee Mountain: Exploring Spiritual Ecology in Western Nepal - Tripathi, Damodar; Thing, Uday; Kaini, Tika Raj (Curriculum Development Journal, 2023)
Fire (Agni in Sanskrit) is one of the central symbols in the Rigveda, the most ancient and the holiest scripture for Hindus. In the Rigvedic constitution, fire symbolism intricately mediates every plane of human existence: from the expansive realms of earth, atmosphere, and sky to the subtle nuances of the corporeal body, breath, and mind. This paper tackles the constitution of fire symbolism in different planes of Panchasee ecology. It argues that the identification of fire as a key symbol in each three planes by Panchasee people is the ‘material manifestation’ of the ideological construction of the Rigvedic fire symbolism living in the rituals and traditions of Panchseee since time immemorial. A fieldwork was conducted between 2020-2022 to get primary details utilized for this study. By situating the cultural practices within the broader anthropological discourse on religion and spirituality, this study enriches our understanding of the interplay between cultural symbolism, ecologicaldynamics, and human consciousness in the Himalayan context.